2016
DOI: 10.1186/s12864-016-2993-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny and expressional profiles of mitogen activated protein kinase kinase kinase (MAPKKK) gene family in bread wheat (Triticum aestivum L.)

Abstract: BackgroundMitogen-activated protein kinase kinase kinases (MAPKKKs) are the important components of MAPK cascades, which play the crucial role in plant growth and development as well as in response to diverse stresses. Although this family has been systematically studied in many plant species, little is known about MAPKKK genes in wheat (Triticum aestivum L.), especially those involved in the regulatory network of stress processes.ResultsIn this study, we identified 155 wheat MAPKKK genes through a genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 51 publications
6
81
0
Order By: Relevance
“…In addition, SBP genes were mapped to corresponding chromosomes to determine their physical position, and we found that SBP genes were widely but not evenly distributed on chromosomes. Similar findings have been reported in other wheat transcription factor families, such as MADS [81], AP2/ERF [82], and MAPKKK [83]. The number of genes on chromosome 7 (23 genes) was the most, whereas the number of genes on chromosome 4 (1 gene) was the least in wheat.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, SBP genes were mapped to corresponding chromosomes to determine their physical position, and we found that SBP genes were widely but not evenly distributed on chromosomes. Similar findings have been reported in other wheat transcription factor families, such as MADS [81], AP2/ERF [82], and MAPKKK [83]. The number of genes on chromosome 7 (23 genes) was the most, whereas the number of genes on chromosome 4 (1 gene) was the least in wheat.…”
Section: Discussionsupporting
confidence: 87%
“…A phosphoproteomic analysis in maize identified hundreds of male sterility-associated proteins which were assumed to form protein complexes with kinases [50]. Regarding the regulation of phosphorylation, the protein kinase gene family as well as the protein phosphatase gene family have been widely studied in model plants and agronomically important crops such as wheat and maize [51,52,53]. It was revealed that plants do not possess typical protein tyrosine kinase genes [51].…”
Section: Systems For Post-translational Modifications In Crops Undmentioning
confidence: 99%
“…Regarding the regulation of phosphorylation, the protein kinase gene family as well as the protein phosphatase gene family have been widely studied in model plants and agronomically important crops such as wheat and maize [51,52,53]. It was revealed that plants do not possess typical protein tyrosine kinase genes [51]. However, protein tyrosine phosphatases were discovered in crops like tomato [54].…”
Section: Systems For Post-translational Modifications In Crops Undmentioning
confidence: 99%
“…Gene expression patterns are usually closely related to their functions [25]. To gain insight into the temporal and spatial expression patterns of CqHsf genes, RNA-seq data of different organs, including seedling, stem, leaf, inflorescence, and dry seeds were downloaded from the NCBI Sequence Read Archive (SRA) database, and then were used to analyze the expression profiles in tissues.…”
Section: Expression Patterns Of Cqhsfs In Different Tissues or Organsmentioning
confidence: 99%
“…The potential members of the quinoa Hsf gene family were identified following the method described by Wang et al [25] with some modifications. Firstly, all the available quinoa protein sequences were obtained from the Ensembl Plants database as a local protein database [26].…”
Section: Identification Of Hsf Genes In the Quinoa Genomementioning
confidence: 99%